2019
DOI: 10.31235/osf.io/vu5ag
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Multilevel Analysis of Predictors of Modern Contraceptive Use among Reproductive Age Women in Sierra Leone: Insight from Demographic and Health Surveys.

Abstract: Background: Variations in the effect of predictors of Sierra Leone women’s use of modern contraceptive from one community to another is unknown. The identified gap was addressed using multilevel logistic regression models.Methods: Pooled 2008 and 2013 Sierra Leone Demographic and Health Surveys datasets were used. Single level logistic regression analyses were conducted on 24,032 women, and multilevel logistic regression models were performed on 23,329 women. Statistical significance was pegged at p≤0.01 and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
6
3
0
Order By: Relevance
“…This study revealed that an increasing educational level of respondents; whose husbands were more likely to use a modern contraceptive method. This result was consistent with previous studies [14,[21][22][23][24][25]. This could be explained by the fact that educated women have better access to health care information, have greater autonomy to make decisions, and have a greater ability to use quality health care services.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study revealed that an increasing educational level of respondents; whose husbands were more likely to use a modern contraceptive method. This result was consistent with previous studies [14,[21][22][23][24][25]. This could be explained by the fact that educated women have better access to health care information, have greater autonomy to make decisions, and have a greater ability to use quality health care services.…”
Section: Discussionsupporting
confidence: 92%
“…In the last full model with both individual and community-level factors accounted for, about 86.69% of the variation was observed for the use of modern contraceptive methods. It was in agreement with studies in Ethiopia [14,21], and Nigeria [22].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations